Let A be the sum of the digits of 4 4 4 4 4 4 4 4 and B be the sum of digits of A . Find the sum of digits of B .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
@Mark Hennings Sir how did you calculate those logarithmic values? And the leading digit of the number?
Log in to reply
lo g 1 0 4 4 4 4 4 4 4 4 = 4 4 4 4 lo g 1 0 4 4 4 4 can be evaluated on any scientific calculator. Then 4 4 4 4 4 4 4 4 = 1 0 0 . 7 0 7 8 8 × 1 0 1 6 2 1 0 ≈ 5 . 1 × 1 0 1 6 2 1 0 and 1 0 0 . 7 0 7 8 8 can be evaluated on any scientific calculator.
Log in to reply
Thankyou sir.!! :) :)
Log in to reply
@Ankit Kumar Jain – A calculator-free approach would be to note that 4 4 4 4 < 2 1 0 0 0 0 , and that 2 4 > 1 0 , so that 4 4 4 4 4 4 4 4 < 2 4 4 4 4 1 0 4 × 4 4 4 4 < 1 0 1 1 1 1 1 0 4 × 4 4 4 4 = 1 0 1 6 6 6 5 Thus A ≤ 1 + 1 6 6 6 5 × 9 = 1 4 9 9 8 6 , B ≤ 1 + 5 × 9 = 4 6 and hence C ≤ 1 3 as before.
On further thought we can even simply say that 4 4 4 4 < 1 0 4 so that 4 4 4 4 4 4 4 4 < 1 0 1 7 7 7 6 , so that A ≤ 9 × 1 7 7 7 6 = 1 5 9 9 8 4 , and hence B ≤ 4 6 and C ≤ 1 3 . Taking the digit sum reduces the size of a number massively, and so even very rough approximations are good enough!
Log in to reply
@Mark Hennings – That was great sir...Thanks a lot.
The mod 9 thing is really cool. It's really only useful once we know that our answer is going to be a single-digit number or so, though. This problem doesn't really seem possible until you realize the surprisingly small magnitude of the solution.
what a machine :D
Problem Loading...
Note Loading...
Set Loading...
If C is the sum of the digits of B , then C ≡ B ≡ A ≡ 4 4 4 4 4 4 4 4 modulo 9 . Now 4 4 4 4 ≡ 7 ( m o d 9 ) and 7 3 ≡ 1 ( m o d 9 ) and 4 4 4 4 ≡ 1 ( m o d 3 ) , so that 4 4 4 4 4 4 4 4 ≡ 7 4 4 4 4 ≡ 7 1 ≡ 7 ( m o d 9 ) Now lo g 1 0 4 4 4 4 4 4 4 4 ≈ 1 6 2 1 0 . 7 0 7 8 8 , so that 4 4 4 4 4 4 4 4 ≈ 5 . 1 × 1 0 1 6 2 1 0 is a 1 6 2 1 1 - digit number with leading digit 5 , and hence A ≤ 5 + 1 6 2 1 0 × 9 = 1 4 5 8 9 5 . But then B ≤ 1 + 5 × 9 = 4 6 , and hence C ≤ 4 + 1 × 9 = 1 3 . Since 1 ≤ C ≤ 1 3 and C ≡ 7 ( m o d 9 ) , we deduce that C = 7 .